Exploring Multi-Hop LoRa for Green Smart Cities - Aslam, Muhammad Shehryar; Khan, Alishba; Atif, Abeera; Hassan, Syed Ali; Mahmood, Aamir; Qureshi, Hassaan Khaliq; Gidlund, Mikael (IEEE network, 2020)
With the growing popularity of IoT-based smart city applications, various long-range and low-power wireless connectivity solutions are under rigorous research. LoRa is one such solution that works in the sub-GHz unlicensed spectrum and promises to provide long-range communication with minimal energy consumption. However, conventional LoRa networks are single-hop, with the end devices connected to a central gateway through a direct link, which may be subject to large path loss and hence render low connectivity and coverage. This article motivates the use of multi-hop LoRa topologies to enable energy-efficient connectivity in smart city applications. We present a case study that experimentally evaluates and compares single-hop and multi-hop LoRa topologies in terms of range extension and energy efficiency by evaluating packet reception ratio (PRR) for various source to destination distances, spreading factors (SFs), and transmission powers. The results highlight that a multi-hop LoRa network configuration can save significant energy and enhance coverage. For instance, it is shown that to achieve a 90 percent PRR, a two-hop network provides 50 percent energy savings as compared to a single-hop network while increasing 35 percent coverage at a particular SF. In the end, we discuss open challenges in multi-hop LoRa deployment and optimization.